DAMPAK PROGRAM SAFE4C TERHADAP KESEJAHTERAAN ANAK DI DESA KANJILO KABUPATEN GOWA - Nur Fadillah Juliana; Idham Irwansyah Idrus; Firdaus W Suhaeb (Social Landscape Journal, 2023)
This study aims to determine 1) Implementation of the SAFE4C program in developing child welfare in Kanjilo Village. (2) The impact of participating in the SAFE4C program in Kanjilo Village. This type of research is descriptive qualitative, the determination of informants using a purposive sampling technique with informant criteria has been determined. In data collection techniques, observations, interviews, and documentation. As well as data analysis to reduce data, present data, and draw conclusions. The results of this study indicate: (1) The implementation of the SAFE4C Program went through three stages, (a) Planning for a location recommendation program from DP3A, village communication, outreach, virtual meetings with potential facilitators, and communication, (b) Education program about parenting and training of handling problems involving children, (c) Follow-up  Outreach to schools Programs, implement and strengthen the step of handling children's problems and provide education related to children by the foundation. (2) The impact  from participating in SAFE4C program at Kanjilo Village can be seen in two ways. (a) The positive impact can add insight into children's problems and their handling, the step of problem-solving and the education provided shows a reduction in cases of child problems and Kanjilo Village is increasingly independent in solving child problems (b) the negative impact is more on the participants who are less conducive and embarrassed to tell stories, and the program is short-term in nature and depends on the coordination of the respective Villages after the program is finished.